Interevaluator and Intraevaluator Reliability of Chest Wall Mobility Assessment in Young Asthmatics Subjects. Issue 2 (19th April 2022) - Garcia-Araujo, Adriana S.; Trimer, Renata; da Luz Goulart, Cassia; Caruso, Flavia R.; Ricci, Paula A.; Borghi–Silva, Audrey
Abstract : Purpose: To evaluate interrater and intrarater reliability of chest wall mobility using cirtometry in individuals with asthma and controls. Methods: Twenty-six controlled individuals with asthma group (AG) and 12 healthy individuals control group (CG) underwent chest wall mobility assessed by cirtometry. The measurements were performed manually by 2 independent evaluators at 3 levels: axillary, xiphoid and abdominal using a tape, in 2 different days. For the analyses, the average of 3 measurements and the highest value were considered. Results: Interrater reliability in AG showed acceptable intraclass correlation coefficient (ICC) for the axillary (0.76 and 0.75), good for the xiphoid (0.91 and 0.93), and abdominal level (0.91 and 0.91) for the average and highest value. In CG, ICC values were acceptable for the 3 levels: axillary (0.64 and 0.71), xiphoid (0.66 and 0.93), and abdominal level (0.61 and 0.91) also for the average and highest value. The analysis with the mean and the highest values found it acceptable for the axillary and good for the xiphoid and abdominal levels. Intrarater ICC was good for all levels in AG, axillary (0.86), xiphoid (0.93), and abdominal (0.96), for both evaluators. In CG, for evaluator 1, it was acceptable for the axillary and good for the xiphoid and abdominal levels. Regarding evaluator 2, it was good for the axillary and xiphoid and acceptable at the abdominal level. Conclusion: Cirtometry is a reliable tool to measure the chest wall mobility in controlled asthma individuals and in healthy individuals. The average of the 3 measurements or the highest value of the evaluations may be considered in clinical assessments. Axillary mobility was lower in the asthma group.